The Influence of Company Size, Capital Structure and Enterprise Risk Management on the Value of Companies Listed on the Indonesia Stock Exchange (IDX) 2014-2018.: Pengaruh Ukuran Perusahaan, Struktur Modal dan Enterprise Risk Management Terhadap Nilai Perusahaan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2014-2018. - Rima Mei Virdiani; Wisnu Setiyono (Universitas Muhammadiyah Sidoarjo, 2021)
This research was conducted to apply the Influence of Company Size, Capital Structure and Enterprise Risk Management on the Value of Companies Listed on the Indonesia Stock Exchange (IDX) in 2013-2018. This research is a quantitative research type. The sampling technique used is purposive sampling. The sample used is 60 with the number of companies as many as 12 companies. The analytical tool used is Eviews version 10. This data was analyzed by, Classical Assumption Test, Panel Data Regression, T-Test, F-Test, and R2 Test. The results of this study indicate that firm size has a significant effect on firm value in construction companies listed on the Indonesia Stock Exchange. Capital structure (DER) does not significantly affect firm value on construction companies listed on the Indonesia Stock Exchange. Enterprise Risk Management (ERM) has a significant effect on firm value in construction companies listed on the Indonesia Stock Exchange.